Mineralogy - René, Miloš (IntechOpen, 2022)
Mineralogy includes thirteen chapters that discuss the methodology of specific mineralogical methods, the composition of minerals from different igneous rocks, and the composition of minerals from different sedimentary rocks.It contains detailed mineralogical studies from Africa, Asia, and Europe. Chapters present different scientific mineralogical methods and detailed descriptions of minerals from different magmatic and sedimentary rocks.